D-dimer levels and the disseminated intravascular coagulation score to predict severity and outcomes in sepsis or septic shock - Schupp, Tobias; Weidner, Kathrin; Rusnak, Jonas; Jawhar, Schanas; Forner, Jan; Dulatahu, Floriana; Brück, Lea Marie; Hoffmann, Ursula; Kittel, Maximilian; Bertsch, Thomas; Akın, Ibrahim; Behnes, Michael (Clinical laboratory, 2023)
Background: Studies investigating the diagnostic and prognostic value of D-dimer levels and the disseminated in-travascular coagulation (DIC) score in sepsis or septic shock commonly include preselected subgroups of patients or were published prior to the current sepsis-3 criteria. Therefore, this study investigates the diagnostic and prog-nostic impact of D-dimer levels and the DIC score in patients with sepsis and septic shock. Methods: Consecutive patients with sepsis and septic shock enrolled in the prospective and monocentric "MARSS" registry from 2019 to 2021 were included. First, the diagnostic value of D-dimer levels was compared to the DIC score to discriminate patients with septic shock from patients with sepsis without shock. Thereafter, the prognostic value of D-dimer levels and the DIC score was tested for 30-day all-cause mortality. Statistical analyses included univariable t-tests, Spearman ' s correlations, C-statistics, Kaplan-Meier, as well as uni-and multivariable cox regression analyses. Results: One hundred patients were included (n = 63 with sepsis and n = 37 with septic shock). The overall rate of all-cause mortality at 30 days was 51%. With an area under the curve (AUC) of 0.710 and 0.739, both D-dimer level and the DIC score revealed reliable diagnostic accuracy for the discrimination of septic shock. However, D-dimer levels and the DIC scores were shown to have poor to moderate prognostic accuracy (AUC 0.590 -0.610) with regard to 30-day all-cause mortality. Specifically, very high D-dimer levels (i.e., > 30 mg/L) (HR = 2.648; 95% CI 1.147 -6.112; p = 0.023) and a DIC scores >= 3 (HR = 2.095; 95% CI 1.095 -4.009; p = 0.0258) were associ-ated with highest risk of 30-day all-cause mortality. Finally, both higher D-dimer levels (HR = 1.032; 95% CI 1.005 -1.060; p = 0.021) and DIC scores (HR = 1.313; 95% CI 1.106 -1.559; p = 0.002) were associated with in-creased risk of 30-day all-cause mortality after multivariable adjustment. Conclusions: Both D-dimer levels and the DIC scores revealed reliable diagnostic accuracy for the discrimination of septic shock, but a poor to moderate prognostic value for the discrimination of 30-day all-cause mortality. Espe-cially very high D-dimer levels (i.e., > 30 mg/L) and a DIC score >= 3 were associated with highest risk of 30-day all-cause mortality.